The Role of Reading Self-Efficacy in Enhancing High School Students’ Comprehension of Argumentative Texts - Afina Ulya Taufiq; Ratmanida Ratmanida (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading self-efficacy is believed to influence students’ engagement and success in comprehending complex texts, particularly argumentative texts that demand higher-order thinking. However, its specific contribution remains underexplored in the Indonesian EFL context. This study employed a correlational design to examine the contribution of reading self-efficacy to the comprehension of argumentative texts among senior high school students. Data were collected from 125 twelfth-grade students across four public schools in Padang City using a reading comprehension test and a self-efficacy questionnaire. To enrich the quantitative findings, brief follow-up interviews were conducted with selected participants. Statistical analysis using simple linear regression revealed that reading self-efficacy significantly contributed 9.83% to students’ reading comprehension scores, indicating a modest but meaningful relationship (p 0.05). Qualitative data supported this finding, showing that students’ perceptions of personal progress, emotional responses, peer comparison, and strategy use shaped their self-efficacy. Students with high self-efficacy reported greater persistence and more effective reading strategies, while those with lower self-efficacy expressed anxiety and limited engagement with text content. The findings suggest that while reading self-efficacy does not fully predict comprehension outcomes, it plays a crucial motivational role, particularly when students face cognitively demanding texts. The results underscore the importance of fostering self-belief alongside strategy instruction in reading classrooms. Given the limited geographic scope, future research should include broader populations and additional variables to enhance generalizability.